2016
DOI: 10.1016/j.devcel.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

SAPCD2 Controls Spindle Orientation and Asymmetric Divisions by Negatively Regulating the Gαi-LGN-NuMA Ternary Complex

Abstract: Control of cell-division orientation is integral to epithelial morphogenesis and asymmetric cell division. Proper spatiotemporal localization of the evolutionarily conserved Gαi-LGN-NuMA protein complex is critical for mitotic spindle orientation, but how this is achieved remains unclear. Here we identify Suppressor APC domain containing 2 (SAPCD2) as a previously unreported LGN-interacting protein. We show that SAPCD2 is essential to instruct planar mitotic spindle orientation in both epithelial cell cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 38 publications
0
39
2
Order By: Relevance
“…However, in epidermis, we and others have shown that LGN forms an apical complex with Insc, Gαi3, NuMA, dynactin and Par3 and that LGN loss leads to loss of perpendicular divisions, impaired Notch signaling and lethal defects in epidermal barrier formation and differentiation (Lechler and Fuchs, 2005;Poulson and Lechler, 2010;Williams et al, 2011Williams et al, , 2014. Similar roles for LGN in promoting perpendicular/ asymmetric divisions have been reported in retina and mammary gland (Ballard et al, 2015;Chiu et al, 2016;Lacomme et al, 2016). The molecular mechanisms that regulate the differential subcellular localization of LGN in progenitors undergoing both symmetric and asymmetric cell divisions remain largely unknown.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, in epidermis, we and others have shown that LGN forms an apical complex with Insc, Gαi3, NuMA, dynactin and Par3 and that LGN loss leads to loss of perpendicular divisions, impaired Notch signaling and lethal defects in epidermal barrier formation and differentiation (Lechler and Fuchs, 2005;Poulson and Lechler, 2010;Williams et al, 2011Williams et al, , 2014. Similar roles for LGN in promoting perpendicular/ asymmetric divisions have been reported in retina and mammary gland (Ballard et al, 2015;Chiu et al, 2016;Lacomme et al, 2016). The molecular mechanisms that regulate the differential subcellular localization of LGN in progenitors undergoing both symmetric and asymmetric cell divisions remain largely unknown.…”
Section: Discussionmentioning
confidence: 70%
“…Here we have examined one candidate and show a weaker concordance between LGN and Gαi3 in DT than in other regions. Other potential regulators of LGN cortical localization include Insc, the LGN homolog Ags3 (Gpsm1), Sapcd2, afadin (Mllt4), 4.1G/R (Epb41l2/ Epb41), 14-3-3 proteins, Par3 and aPKC (Prkcι) (Sanada and Tsai, 2005;Hao et al, 2010;Postiglione et al, 2011;Kiyomitsu and Cheeseman, 2013;Niessen et al, 2013;Seldin et al, 2013;Williams et al, 2014;Carminati et al, 2016;Chiu et al, 2016). Owing to the diverse patterns of LGN localization found in filiform papillae, we believe that the DT represents an ideal system with which to address this important question in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies add further complexity to our understanding of the spindle orientation mechanism by revealing the involvement of additional factors (for example, SAPCD2, microRNAs, and peroxisomes); however, it remains unclear precisely how these components incorporate into and facilitate this process 14, 57, 58 . Additional studies have revealed interesting and unexpected context-dependent variations in pathway regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In most epithelia, LGN is excluded from the apical cortex by apically localized factors such as the polarity protein atypical protein kinase C (aPKC), which phosphorylates LGN, and SAPCD2, which competes with NuMA for binding to LGN, thus orienting spindles parallel to the epithelial plane 13, 14 . In some systems, however, LGN is recruited to the apical domain through binding to Insc, which interacts with the Par3 polarity protein 15 .…”
Section: Spindle Orientation Mechanismmentioning
confidence: 99%
“…To generate DVL TKO cells, HEK293T cells (Chiu et al, 2016; not authenticated) were transfected with plasmids encoding Cas9 and guide RNAs (Ran et al, 2013) targeting genomic loci of DVL ( DVL1/2 , 5′-CTACATTGGCTCCATCATGA; DVL3 , 5′-ACCATGCTTCAATGGCCGGG) or LRP6 ( LRP6 , 5′-CGATTGGTTGATGCTACAAA); clones were screened by immunoblotting, and deletions were confirmed by genomic DNA sequencing. To generate stable DVL2-expressing cell lines, DVL TKO cells were transfected with 200 ng DVL2–GFP pBabePURO:PEI (1:3), and selected with 2 µg/ml puromycin.…”
Section: Methodsmentioning
confidence: 99%